Influence of the amino acid and fractional composition it dry milk of mammals on the digestibility of dry milk mixtures - Falendysh, Natalia; Belinska, Kristina; Bobel (Zinchenko), Inna; Adamczyk, Greta (My University, 2022)
Use of goat, mare, sheep dry milk and dry milk mixtures for baby food were studied. Amino acid composition was determined by ion exchange chromatography; fractional composition by electrophoresis; digestibility of dry milk mixtures was studied in vitro. The limiting amino acid of dry cow and sheep’s milk proteins is cystine, the amino acid scores of which are 46.0% and 47.0%, respectively. The amino acid and fractional composition of proteins of dry mare milk is close to composition of human milk proteins, so the digestibility of products based on mare milk is similar to that of human milk

Досліджено використання козячого, кобилячого, овечого сухого молока та сухих молочних сумішей для дитячого харчування. Амінокислотний склад визначали методом іонообмінної хроматографії; фракційний склад за допомогою електрофорезу; засвоюваність сухих молочних сумішей вивчали in vitro. Лімітуючою амінокислотою сухих білків коров’ячого та овечого молока є цистин, амінокислотний скор якого становить 46,0% та 47,0% відповідно. Амінокислотний і фракційний склад білків сухого кобилячого молока близький до складу білків жіночого молока, тому засвоюваність продуктів на основі кобилячого молока подібна до жіночого
Keywords: milk; sheep; amino acid; protein; молоко; вівці; амінокислоти; білок; кафедра технології хлібопекарських і кондитерських виробів